2018
DOI: 10.1177/1091581818809473
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Mutagenicity Evaluation Following RISUG Contraception Reversal in Rats

Abstract: Reestablishment of fertility, after a male contraceptive method, is of great concern. In this context, RISUG (Reversible Inhibition of Sperm Under Guidance) has been evaluated for its mutagenicity following reversibility with dimethyl sulfoxide (DMSO)/sodium bicarbonate (NaHCO3) in Wistar albino rats. Animals were divided into 7 groups, namely, sham-operated control, vas occlusion with RISUG for 90 and 360 days, reversal with DMSO and NaHCO3 after 90 and 360 days, respectively. The testis, cauda epididymis, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…RISUG affects the sperm membrane including the acrosome which may have resulted in the sperm losing its fertilizing ability222324. Successful reversal of RISUG injection has been observed in rat, rabbit and langur monkeys’ studies without any side effects2526272829303132. However, reversibility of fertilizing ability of sperms was not attempted in this study.…”
Section: Discussionmentioning
confidence: 89%
“…RISUG affects the sperm membrane including the acrosome which may have resulted in the sperm losing its fertilizing ability222324. Successful reversal of RISUG injection has been observed in rat, rabbit and langur monkeys’ studies without any side effects2526272829303132. However, reversibility of fertilizing ability of sperms was not attempted in this study.…”
Section: Discussionmentioning
confidence: 89%
“…It is also concluded that vas occlusion with RISUG ® at the contraceptive dose regimen is not associated with genotoxicity in leukocytes or the testis of pre-and post-reversal rats [61]. The study using both DMSO and NaHCO 3 for reversal of RISUG ® -induced contraception was successful without any toxicity at the cellular levels [62]. ii.…”
Section: Advantages Of Risug ® Over Other Methods Of Male Contraceptionmentioning
confidence: 92%
“…Currently, there are two NH-IVIG prototypes: Vasalgel and reversible inhibition of sperm under guidance (RISUG). The flexible, clear-colored hydrogels are composed of dimethyl sulfoxide and dissolved styrene-alt-maleic acid (Vasalgel) or styrene-alt-maleic anhydride with or without iron oxide and copper (RISUG) (Ansari, Hussain, Khan, Badar, & Lohiya, 2018;Colagross-Schouten, Lemoy, Keesler, Lissner, & VandeVoort, 2017;Jha, Jha, & Guha, 2009;Waller, Bolick, Lissner, Premanandan, & Gamerman, 2016). NH-IVIG is administered via an outpatient procedure wherein a medical professional performs minimally invasive, no-scalpel scrotal incisions and bilaterally injects NH-IVIG into a section of the lumen of each vas deferens (Ansari, Hussain, Khan, & Lohiya, 2016;Kanakis & Goulis, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Early NH-IVIG data show efficacy percentages comparable to available LARCs and confirmed single doses can possibly last one year (Vasalgel) to over a decade (RISUG) (Colagross-Schouten et al, 2017; Kanakis & Goulis, 2015;Waller et al, 2016;Waller, Bolick, Lissner, Premanandan, & Gamerman, 2017). Reversibility through urethral expulsion has been achieved by sodium bicarbonate flushes, applying vibration and palpation, or heating with microwaves Ansari, Hussain, et al, 2018;Jha et al, 2009;Waller et al, 2017). NH-IVIGs have shown minor local side effects, tested negative for genotoxicity or mutagenicity, and generated fewer complications than other experimental methods or vasectomies Ansari, Hussain, et al, 2018;Colagross-Schouten et al, 2017;Waller et al, 2016Waller et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation